(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
The study was made to identify the association of yield and stolon characters and their direct and indirect effects in panikachu, Colocasia esculenta (L.) Schott. The stolon number, single stolon weight, total stolon weight, stolon length, length and breadth of corm and weight of corm showed positive correlation with yield per plant of which single stolon weight and corm breadth showed significant positive correlation with yield per plant at phenotypic level. Stolon breadth exhibited significant positive correlation with yield per plant at genotypic level. The residual effect in the genotypic level was 0.2205 which indicated this character contributed 78% of the yield. Results obtained suggested that maximum emphasis should be given on characters in selecting panikachu genotypes with higher yield per plant and the residual effect in phenotypic level was 0.4235 indicating 58% variability contributed by these characters. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17552 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 131-137, 2013